FAKTOR-FAKTOR PENGARUH KINERJA PERMUKIMAN SEBAGAI ANTISIPASI PERWUJUDAN KAMPUNG WISATA BAHARI - Edi Purwanto; Bambang Setioko; Deasy Olivia (Diponegoro University, 2017)
Tambaklorok is a fishermen kampong located in Tanjungmas, North Semarang. This settlement is known for its fish landing base where people daily come to buy marine products. The population of the kampong which was purely consisted of traditional fishermen at first is recently turning into mixed population with its problems like poverty and bad infrastructures that make this place unhealthy to live. However, behind these problems, this area also has a potency to be a maritime tourist object. The purpose of this research is to find influence factors of fishermen settlement performance as the implementation of the plan to create a maritime tourism kampong that was made by Semarang Municipality in 2015. This research used positivistic research paradigm with quantitative approach, and for processing data, it used statistical test with factor analysis. Based on statistical test and analysis, there are 6 influence factors of fishermen settlement performance that potentially support the development of the maritime tourism kampong.